1994
DOI: 10.1007/bf00177825
|View full text |Cite
|
Sign up to set email alerts
|

The dichotomous size variation of human complement C4 genes is mediated by a novel family of endogenous retroviruses, which also establishes species-specific genomic patterns among Old World primates

Abstract: The human complement C4 genes in the HLA exhibit an unusual, dichotomous size polymorphism and a four-gene, modular variation involving novel gene RP, complement C4, steroid 21-hydroxylase (CYP21), and tenascin-like Gene X (RCCX). The C4 gene size dichotomy is mediated by an endogenous retrovirus, HERV-K(C4). Nearly identical sequences for this retrotransposon are present precisely at the same location in the long C4 genes from the tandem RCCX Module I and Module II. Specific nucleotide substitutions between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 47 publications
3
105
0
Order By: Relevance
“…The size of the B-up clone, 6.8 kb, was indicative of the short C4B gene, which was missing the HERV-K(C4) retrovirus integration (6). This PCR size confirms TaqI results, indicating that all of the patient's C4B genes are short.…”
Section: Search For Novel Mutation In the Proband's Mutant C4b Genesupporting
confidence: 59%
See 2 more Smart Citations
“…The size of the B-up clone, 6.8 kb, was indicative of the short C4B gene, which was missing the HERV-K(C4) retrovirus integration (6). This PCR size confirms TaqI results, indicating that all of the patient's C4B genes are short.…”
Section: Search For Novel Mutation In the Proband's Mutant C4b Genesupporting
confidence: 59%
“…Oligonucleotides of human C4 and RCCX constituents were designed based on published DNA sequences (51)(52)(53) 1,3,4,5,6,8,9,10,11,12,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,31,32,33,34,35,37,38,39,40, and 41. The primers were designed based on the genomic DNA sequence of C4A3a (51).…”
Section: Synthetic Dna Primersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that the reversely oriented HERV-K(C4) in the intron 9 of the long C4 gene would lead to the production of an antisense transcript of the ancient retrovirus whenever the long C4 gene is transcribed (21). This antisense retroviral RNA transcript with multiple defective mutations could confer the host selection advantage in the defense against retroviral infections.…”
Section: The Significance and Implication Of The Long And Short C4 Genesmentioning
confidence: 99%
“…Each C4A or C4B gene may be 21 kb (long) or 14.6 kb (short) in size (20). The long C4 gene contains a 6.36-kb endogenous retrovirus HERV-K(C4) in its intron 9 (21,22). Recently, we showed that the bimodular RCCX haplotypes constitute slightly more than two-thirds of the Caucasian population in the midwestern United States, while the frequencies of monomodular and trimodular RCCX haplotypes were 0.17 and 0.14, respectively (18).…”
mentioning
confidence: 99%